Analisis Pengaruh Kualitas Sistem Media Elektronik E-Filling dan E-Billing Terhadap Tingkat Kepuasan Wajib Pajak (Studi Pada Wajib Pajak di Fakultas Ekonomi Universitas Tridinanti Palembang) - Dimas Pratama Putra; Padriyansyah (JRB-Jurnal Riset Bisnis, 2019)
This research is being done to taxpayers at economic faculty of Tridinanti Palembang. This research aims to know effect the quality of the e-filing and e-billing system toward taxpayers satisfaction level. The population in this study is 339 taxpayers. Sample of 130 taxpayers by using purposive sampling methods. The analytical technique used is a descriptive analysis and conducted a asumsi klasik test. The result of this study is (1). The quality of the e-filing system has a significant positive effect on the degree of taxpayers satisfaction, (2). The quality of the e-filing system has a significant negative effect on the degree of taxpayers satisfaction, dan (3). The quality of e-filing and e-billing system collectively has a significant positive effect on the rate of taxpayers satisfaction.